Assessment of Microbial Contamination on Keyboards and Mice of Computers in Administrative Office in Surman City - Siham Ali (AlQalam Journal of Medical and Applied Sciences, 2024)
This study aimed to assess the level of microbial contamination on keyboards and mice used in administrative office in Sorman City. Samples were collected from 14 keyboards and 14 mice. Microbial analysis involved isolating and identifying bacteria using microscopic, cultural, and biochemical tests. A total of 28 samples were analyzed, revealing contamination with various bacteria. Staphylococcus aureus was the most prevalent, found in 96.42% of samples, with a higher contamination rate on keyboards (100%) compared to mice (92.85%). Other bacteria isolated included Staphylococcus epidermidis (28.57%), Streptococcus species (42.85%), Escherichia coli (14.28%), Klebsiella species. (10.71%), and Salmonella species. (21.42%). The high contamination rates, especially for Staphylococcus aureus, suggest that keyboards and mice are significant reservoirs for pathogens. Staphylococcus epidermidis and Streptococcus species were also commonly found, indicating potential routes of infection through contact with contaminated surfaces. Gram-negative bacteria such as Escherichia coli, Klebsiella species., and Salmonella species. were less prevalent but still notable, potentially due to fecal contamination or food residues. The study highlights the critical need for regular cleaning and disinfection of computer equipment to reduce microbial contamination. Improved hygiene practices are essential to prevent the spread of infections in office environments. هدفت هذه الدراسة إلى تقييم مستوى التلوث الميكروبي على لوحات المفاتيح والفأرات المستخدمة في المكاتب الإدارية في مدينة صرمان. حيث تم جمع عينات من 14 لوحة مفاتيح و14 فأرة. شمل التحليل الميكروبي عزل وتحديد البكتيريا باستخدام الفحوصات الميكروسكوبية والبيوكيميائية. وكشفت النتائج تحليل 28 عينة عن تلوث بكتيري بأنواع مختلفة. كانت Staphylococcus aureus هي الأكثر انتشارًا، حيث وجدت في 96.42% من العينات، مع معدل تلوث أعلى على لوحات المفاتيح (100%) مقارنة بالفأرات (92.85%). كما تم عزل بكتيريا أخرى تشمل Staphylococcus epidermidis (28.57%)، وStreptococcus species (42.85%)، وEscherichia coli (14.28%)، وKlebsiella species. (10.71%)، وSalmonella species. (21.42%). وتشير معدلات التلوث العالية، خاصة لـ Staphylococcus aureus، إلى أن لوحات المفاتيح والفأرات تشكل مصدر هامة للميكروبات. كما تم العثور على Staphylococcus epidermidis وStreptococcus species بشكل شائع، مما يدل على احتمال انتقال العدوى من خلال الأسطح الملوثة. بينما كانت البكتيريا السالبة الجرام مثل Escherichia coli وKlebsiella species. وSalmonella species. أقل شيوعًا، إلا أن وجودها لا يزال ملحوظًا، وربما يكون بسبب التلوث البرازي أو بقايا الطعام. وتسلط الدراسة الضوء على الحاجة الملحة لتنظيف وتعقيم معدات الكمبيوتر بانتظام لتقليل التلوث الميكروبي. تعتبر تحسينات ممارسات النظافة أساسية للوقاية من انتشار العدوى في بيئات المكاتب